5. Classification of DE Delivery Systems - Belyk, Diane; Schubert, Jeremy; Baggaley, Jon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
For their optimal use in distance education (DE), online educational applications need to be integrated within a comprehensive course management system (CMS). Such systems are server-based software that supports the development, delivery, administration, and evaluation of online learning environments. The selection of an appropriate CMS should be considered from the multiple perspectives of the student, the course developer, the course instructor/ tutor, the technical support staff, and the DE institution’s administration. The current evaluation of CMS packages was conducted by a team of individuals with experience and contacts in relation to each of these DE user types. The report compares a series of CMS packages in terms of their range of features, and in relation to their satisfaction of international online education standards.